PENGARUH GAYA HIDUP, FITUR, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG (Value : Jurnal Manajemen dan Akuntansi, 2022)
The fulfillment of a organisation in influencing product buying selections via way of means of having precise conversation with customers, constructing precise product brands, and innovating new merchandise which are owned via way of means of following modern trends. This observe objectives to decide whether or not the have an effect on of Lifestyle, Features, Price, and Promotion at the choice to buy a Samsung emblem cellphone amongst Udinus Semarang students. This study used a statistical series approach based on questionnaires with a total sample of 100 Udinus students. The survey population consisted of her Udinus students using Samsung smartphones. Samples had been taken via way of means of purposive sampling approach. The statistics evaluation technique used is the take a look at at the statistics, the classical assumption take a look at, and the more than one regression take a look at. And the statistics could be processed the use of IBM SPSS 24 software. The outcomes of this observe suggest that lifestyle, features, and promotions have a tremendous impact on Samsung cellphone buying selections for udinus students, however charge does now no longer have a tremendous impact on Samsung cellphone buying selections for udinus students.Keywords: Lifestyle, Features, Price, Promotion